Failure Mode of Lithium Metal Batteries with a Block Copolymer Electrolyte Analyzed by X-Ray Microtomography. Issue 7 (17th April 2015) - Devaux, Didier; Harry, Katherine J.; Parkinson, Dilworth Y.; Yuan, Rodger; Hallinan, Daniel T.; MacDowell, Alastair A.; Balsara, Nitash P.
Abstract : Solid block polymer electrolytes are promising candidates for the development of high energy density rechargeable lithium metal based batteries. All solid-state batteries comprising lithium metal negative electrode and lithium iron phosphate (LiFePO4 ) composite positive electrode were assembled. A polystyrene- b -poly(ethylene oxide) (SEO) copolymer doped with a lithium salt was used as the electrolyte. After cycling the batteries, the reason for capacity fade and failure was determined by imaging the batteries using synchrotron hard X-ray microtomography. These experiments revealed partial delamination of the lithium foil and the block copolymer electrolyte layer. The void volume between the foil and electrolyte layer obtained after 40 to 90 cycles is comparable to volume change in the battery during one cycle. A simple model to account for the effect of delamination on current density in the battery is presented. Capacity fade and battery failures observed in our experiments are consistent with this model. No evidence of lithium dendrite formation was found. In contrast, cycled lithium-lithium symmetric cells with the same polymer electrolyte at the same current density failed due to dendrite formation. No evidence of delamination was found in these cells.